Serum Chemokine CXCL7 as a Potential Novel Biomarker for Obstructive Colorectal Cancer - Li, Longhai; Zhang, Lihua; Zhang, Ting; Qi, Xiaowei; Cheng, Gang; Xia, Lingxia (Frontiers in Oncology, 2021)
Due to the lack of typical symptoms and signs and sensitive indicators for early diagnosis of obstructive colorectal cancer (OCRC), it is critically needed to find new novel biomarkers to ameliorate the management of OCRC patients. In this study, 472 blood samples were collected and measured by enzyme-linked immunosorbent assay (ELISA) to investigate the value of serum chemokine ligand 7 (CXCL7) in diagnosis and prognosis for OCRC patients. The median concentrations of CXCL7 in non-OCRC and OCRC were both higher than that in controls (both P < 0.05). Importantly, the median serum concentration of CXCL7 in OCRC was also higher than that in non-OCRC (P < 0.001). In all OCRC patients, the aera under the curve (AUC) of CXCL7 was 0.918. Combined diagnosis results of logistic regression model were AUC 0.980 and cutoff value 2.29 ng/ml. Similarly, CXCL7 had a higher AUC than other markers when the diagnostic test was carried out in OCRC and non-CRC patients (AUC: 0.689). The concentration of CXCL7 in 40 postoperative OCRC patients was higher than normal people and lower than preoperative patients. The median survival time was 62.00 months and the 5-year overall survival (OS) rate of the patients was 51.80 % in all 155 OCRC patients. Multivariate cox proportional hazard regression models analysis showed that high CXCL7 in serum were independent factors associated with poor OS of OCRC patients (HR=2.216, P=0.032). These results demonstrate that serum CXCL7 may be a potential biomarker both in diagnosis and prognosis for OCRC patients.